2018
DOI: 10.1093/mnras/sty2618
|View full text |Cite
|
Sign up to set email alerts
|

MAHALO Deep Cluster Survey II. Characterizing massive forming galaxies in the Spiderweb protocluster at z = 2.2

Abstract: This paper is the second in a series presenting the results of our deep Hα-line survey towards protoclusters at z > 2, based on narrow-band imaging with the Subaru Telescope. This work investigates massive galaxies in a protocluster region associated with a radio galaxy (PKS 1138−262), the Spiderweb galaxy, at z = 2.2. Our 0.5 mag deeper narrow-band imaging than previous surveys collects a total of 68 Hα emitters (HAE). 17 out of the 68 are newly discovered protocluster members. First, a very high characterist… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 59 publications
(70 citation statements)
references
References 253 publications
(443 reference statements)
2
68
0
Order By: Relevance
“…All these results suggest that we are witnessing the first stages of the wellknown environmental quenching found in lower redshift and/or more evolved clusters (e.g. Tran et al 2009;Alberts et al 2014;Newman et al 2014;Nantais et al 2016;Ji et al 2018;Lee-Brown et al 2017;Noirot et al 2018;Paulino-Afonso et al 2018;Shimakawa et al 2018), which originates the excess of red sources in local galaxy clusters (Dressler 1984).…”
Section: Environmental Quenchingmentioning
confidence: 52%
See 3 more Smart Citations
“…All these results suggest that we are witnessing the first stages of the wellknown environmental quenching found in lower redshift and/or more evolved clusters (e.g. Tran et al 2009;Alberts et al 2014;Newman et al 2014;Nantais et al 2016;Ji et al 2018;Lee-Brown et al 2017;Noirot et al 2018;Paulino-Afonso et al 2018;Shimakawa et al 2018), which originates the excess of red sources in local galaxy clusters (Dressler 1984).…”
Section: Environmental Quenchingmentioning
confidence: 52%
“…The effects of the environment are more evident when looking at the fraction of quenched galaxies. The larger number of massive gas-poor galaxies (ALMA non-detections) in the proto-clusters in comparison to the field (Figures 4 and 7) suggests that these protocluster galaxies are undergoing an accelerated evolution (see also Hayashi et al 2018;Shimakawa et al 2018;Wang et al 2018). These massive gas-poor systems have low gas mass fractions of f gas 6 − 10 % (Figure 4) and red colors ( Figures 5 and 6) which are in agreement with those found for post-starburst and quiescent galaxies at lower redshifts (e.g.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…More recently, radio loud AGNs have been used to trace both low-and high-z clusters and protoclusters (e.g. Blanton et al 2003;Galametz et al 2012;Wylezalek et al 2013Wylezalek et al , 2014Castignani et al 2014;Rigby et al 2014;Blanton et al 2015;Cooke et al 2015Cooke et al , 2016Noirot et al 2016;Paterno-Mahler et al 2017;Shen et al 2017;Noirot et al 2018;Shimakawa et al 2018;Croston et al 2019;Garon et al 2019;Moravec et al 2019;Golden-Marx et al 2019;Moravec et al 2020b). For example, the Clusters Around Radio Loud AGN (CARLA) survey found that ≈ 55% of their 387 radio loud AGNs at 1.3 < z < 3.2 were in overdense environments at the level of 2σ, with 10% of sources in overdense environments at the 5σ level when compared to a background field (Wylezalek et al 2013).…”
mentioning
confidence: 99%